Analisis Persepsi Siswa terhadap Pentingnya Matematika dalam Kehidupan Sehari-Hari di Dua Kelas SMAN 1 Cigugur - Andini, Risa Nur; Yusritawati, Ita; Yanti, Rohmah; Saraswati, Laras (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Mathematics is a fundamental and crucial subject for the development of scientific knowledge and the daily lives of students worldwide. This article aims to analyze students' perceptions of the importance of mathematics in the context of daily life, focusing on two classes at SMA N 1 Cigugur. The research adopts a descriptive method with a qualitative approach, involving interviews with mathematics teachers and students, as well as the use of a questionnaire that is later analyzed comparatively. The results of the study indicate that mathematics teachers at SMA N 1 Cigugur strive to make mathematics learning more engaging and applicable, acknowledging that some students find mathematics difficult and tedious. Students understand the relevance of mathematics in their daily lives, such as personal financial management, measuring food ingredients, and problem-solving. Nevertheless, some students still face difficulties in understanding this subject and lack confidence. Teaching methods also play a significant role, with students preferring practical and real-world-relevant approaches. The use of technology in mathematics learning is perceived as helpful in enhancing students' understanding. In conclusion, mathematics plays a crucial role in the daily lives of students; however, challenges in understanding and negative perceptions of this subject still exist